2016
DOI: 10.1128/iai.01305-15
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Cell Response to Fusobacterium nucleatum

Abstract: c Vascular response is an essential aspect of an effective immune response to periodontal disease pathogens, as new blood vessel formation contributes to wound healing and inflammation. Gaining a greater understanding of the factors that affect vascular response may then contribute to future breakthroughs in dental medicine. In this study, we have characterized the endothelial cell response to the common bacterium Fusobacterium nucleatum, an important bridging species that facilitates the activity of late colo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
28
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 49 publications
(44 reference statements)
4
28
0
Order By: Relevance
“…In this study, we demonstrate that F. nucleatum inhibits the proliferation of GMSCs. It has been reported that F. nucleatum can impair endothelial cell and mononuclear cell proliferation, which is consistent with our finding in GMSCs (Haake and Lindemann, 1997;Mendes et al, 2016). Viable and formaldehyde-treated, but not sonicated or heat-treated F. nucleatum bacteria, can cause severe aggregation and apoptosis of peripheral blood mononuclear cells (PBMCs) (Huynh et al, 2011).…”
Section: Discussionsupporting
confidence: 92%
“…In this study, we demonstrate that F. nucleatum inhibits the proliferation of GMSCs. It has been reported that F. nucleatum can impair endothelial cell and mononuclear cell proliferation, which is consistent with our finding in GMSCs (Haake and Lindemann, 1997;Mendes et al, 2016). Viable and formaldehyde-treated, but not sonicated or heat-treated F. nucleatum bacteria, can cause severe aggregation and apoptosis of peripheral blood mononuclear cells (PBMCs) (Huynh et al, 2011).…”
Section: Discussionsupporting
confidence: 92%
“…Under hypoxia condition, hypoxia‐inducible factor‐1 (HIF‐1) increases the expression of angiogenesis growth factors, including vascular endothelial growth factor (VEGF) and its receptors (VEGFRs; Hashemi Goradel et al, ). Consistent with this proposal, Mendes et al () reported that infection of epithelial cells with F. nucleatum increases angiogenesis via upregulating VEGF and VEGFR1 and 2. Another effect of hypoxia and HIF‐1 in tumor microenvironment is related to the promotion of myeloid‐derived suppressor cells (MDSCs), which act as immunosuppressive cells in cancer (Chiu et al, ).…”
Section: Mechanisms Of Actionmentioning
confidence: 58%
“…Vascular response is an essential aspect of an effective immune response to periopathogens (Mendes et al., ). In our study, the higher periodontal and dental tissue loss observed in T1D‐W rats was associated with vascular alteration in PDL.…”
Section: Discussionmentioning
confidence: 99%